ANALYSIS OF THE INFLUENCE OF HARVEST LABOR ON PALM OIL PRODUCTION IN PT. AGRO SYNERGY NUSANTARA–ACEH - Riyand Hadirijal N; Aswin Nasution (RADJA PUBLIKA, 2023)
In the oil palm plantation business, harvesting labor is one of the key factors in the company's success in obtaining maximum production. This research was conducted to determine the effect of harvesting labor on oil palm FFB production. The results analyzed by multiple linear regression showed that the variables age, recent education, work experience, land conditions, harvest premiums, foreman attention, and road conditions had a positive effect on the FFB production of harvest labor. However, the variable family dependents and the distance between the house and the garden have a negative effect. Partially only the variables of age and work experience have a significant effect on the FFB production of harvest labor, but simultaneously all variables have a significant effect. Therefore, to increase the company's FFB production, in terms of harvesting workforce, companies need to pay attention to and maintain harvesting labor as an operational factor by increasing worker capacity.